Partisipasi Masyarakat Terhadap Kebersihan Lingkungan Di Rt 08, Rw 05 Pematang Gubernur,Kota Bengkulu - Milanda, Exsel; Sari, Petlin Yupita; Oktapia, Rosa; Sundari, Oktavia; Hasanah, Mendalia; Yanto, Yanto; Haryono, Mimpira; Mujiono, Mujiono (Jurnal Dehasen Untuk Negeri, 2026)
Community participation is a key factor in maintaining cleanliness and environmental sustainability in residential areas. This research and Community Service Program (KKN) was conducted in RT 08, RW 05 Pematang Gubernur, Bengkulu City to describe the level of community participation in environmental cleanliness efforts, identify driving and inhibiting factors, and formulate recommendations to improve participation. The methods used included field observations, structured interviews with 40 residents, and discussions with RT/RW administrators. The results showed that the level of community participation was in the moderate category. The main driving factors were awareness of family health and support from community leaders, while inhibiting factors included limited supporting facilities and lack of awareness among some residents.